Explanation of the Effective Components in Entrepreneurial Orientation among Students: A Case Study of the Faculty of Agriculture, Razi University - Shahbazi Somayeh (Journal of Global Pharma Technology, 2017)
In spite of the increasing unemployment level and the entrepreneurship need of the agricultural graduates, they do not considerably pay attention to entrepreneurship. Regarding the significance of this issue, the major objective of this study was to explain the effective components in entrepreneurial orientation among Razi University students. The population included 1392 student, of whom 310 people were selected based on simple random sampling. A questionnaire was used as the data collection instrument. The validity of the questionnaire was confirmed by the members of the Faculty of Agriculture, Razi University; the reliability of which was also confirmed as 0.86 by means of SPSS 20. Data were analyzed and 10 effective factors in entrepreneurial orientation were identified, the most important of which was the university structural change with a mean of 3.94. Furthermore, the most important factor of the lack of entrepreneurial orientation was the need for capital and lack of support with the mean of 4.01. The investigation of Razi University students’ entrepreneurial status indicated that most of whom are willing to get employed by the government. Moreover, there was not a difference between the urban and rural students as well as the male and female students in terms of entrepreneurial orientation. However, the single students were more interested in entrepreneurship than the married ones. The results of Chi-square test indicated that major and educational level, age, parents’ jobs, parents’ educational level, gender, marital status, and the living place have a significant relationship with the lack of entrepreneurial orientation at the level of 0.05 percent. According to the results, in addition to governmental support, the goals, methods, and the approaches of the agricultural higher education system are needed to be revised so as to improve the agriculture students’ entrepreneurial orientation.Keywords: Entrepreneurial orientation, Unemployment, Agriculture students, Razi University.